Compound Sentences In The Tripadvisor Reviews - I Gede Adi Yoga Nanda Wiguna Adi; IGB Wahyu Nugraha; I.B.Gde Nova Winarta (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2021)
This study aims to find out the types of coordination in compound sentences and its syntactical structure. The data source was taken from the TripAdvisor reviews of the Padma Legian Resort and Padma Ubud Resort on June until September 2019. The data analyzed by using the descriptive qualitative method and supported with quantitative method. The theory proposed by Quirk and Greenbaum (1973) to find out the types of coordination in compound sentence and the theory proposed by Brown and Miller (1991) to find out the syntactical structure demonstrated by tree diagram. This analyzed  was presented in formal and informal method. As the result of this study shown that there were 3 types of coordination found in the TripAdvisor Reviews of the Padma Legian Resort and Padma Ubud Resort, those were compound sentences using syndetic coordination with 67 data (67%), compound sentence that used asyndetic coordination with 24data (24%) and compound sentence that used both syndetic and  asyndetic coordination with 9 data (9%).